Relation between mechanical and textural properties of dense materials of tetragonal and cubic zirconia - Aglietti, Esteban Fausto (2016)
In the current paper we present a study of the sinterability of two zirconia (ZrO2) nanopowders with different content of yttrium oxide (Y2O3) 3 and 8 % tetragonal and cubic zirconia, respectively. After sintering between 900-1500ºC, the samples were characterized in terms of their density and porosity using Archimedes technique. Their grain size was evaluated using scanning electron microscope (SEM). Vickers hardness and fracture toughness (KIC) were measured by the indentation method. The results showed that pores are almost eliminated at sintering temperatures higher than 1400ºC and grain size is larger due to the agglomerates formed as a result of grain growth. Vickers hardness evaluated at 1400ºC sintering temperature is greater than that obtained at 1500ºC due to the grain growth produced at this temperature. In addition, we show a correlation between Vickers hardness and the porosity, obtained by evaluating empirical and theoretical models.Keywords: Zirconia, Sintering, Vickers hardness.